2003
DOI: 10.4102/sajpsychiatry.v9i1.128
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Afrocentric approach to psychiatry

Abstract: NO ABSTRACT AVAILIBLE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…S. Edwards, 1984;Erdtsieck, 2001;Freeman & Motsei, 1992;Hirst, 1993;Holdstock, 2000;Horton, 1962Horton, , 1967Horton, , 1995O.U.Kalu, 1978;K. Ogbaa, 1992;Magesa, 1998;Mbiti, 1969;D. L. Mkhize, 2003;H.…”
Section: Instances Of Abnormal Behaviour Encountered In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…S. Edwards, 1984;Erdtsieck, 2001;Freeman & Motsei, 1992;Hirst, 1993;Holdstock, 2000;Horton, 1962Horton, , 1967Horton, , 1995O.U.Kalu, 1978;K. Ogbaa, 1992;Magesa, 1998;Mbiti, 1969;D. L. Mkhize, 2003;H.…”
Section: Instances Of Abnormal Behaviour Encountered In Africamentioning
confidence: 99%
“…D. Edwards, 1985;Erdtsieck, 2001;Gobodo, 1990;Hirst, 1993;Holdstock, 1981Holdstock, , 2000K. Ogbaa, 1992;D. L. Mkhize, 2003;Olsson, 1989;Ngubane, 1977;Peek, 1991;Robertson, & Kottler, 1993;Sokhela et al, 1984;Turner, 1968;Whyte, 1981Whyte, , 1997Yoder, 1982), operating, in that case, as the sick person's spokesperson in search of meaning to be attached to his or her illness.…”
Section: Mechanisms Of Clinical Diagnosis Within the Africentric Paramentioning
confidence: 99%
“…It was also found that the more serious and severe the disorders, the more likely they were to go for traditional/spiritual healers. Mkize [35] states that mental health-care services have been in the hands of traditional healers for centuries. For this and other reasons, it is crucial for Western-trained health professionals to work hand in hand with traditional healers.…”
Section: Treatment Choicementioning
confidence: 99%
“…Berg (2003) 50 regarded traditional healers as "highly trained psychotherapists" while also referring to "ubuntu" as depicting humanity and compassion. Mkize DL (2003) 55 saw the way forward to integrate Western and African psychiatry as a system incorporating both approaches based on the core African cultural value of "ubuntu". : "… in the beginning there was uMvelinqangi (the first Being).…”
Section: African Worldviewmentioning
confidence: 99%